2021
DOI: 10.1021/acs.est.0c07474
|View full text |Cite
|
Sign up to set email alerts
|

Katabatic Wind and Sea–Ice Dynamics Drive Isotopic Variations of Total Gaseous Mercury on the Antarctic Coast

Abstract: Clarifying the sources and fates of atmospheric mercury (Hg) in the Antarctic is crucial to understand the global Hg circulation and its impacts on the fragile ecosystem of the Antarctic. Herein, the annual variations in the isotopic compositions of total gaseous Hg (TGM), with 5−22 days of sampling duration for each sample, were presented for the first time to provide isotopic evidence of the sources and environmental processes of gaseous Hg around the Chinese Great Wall Station (GWS) in the western Antarctic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Atmospheric samples, including TGM (typically used to represent GEM) , , and PBM of different particulate sizes (TSP, PM 10 , and PM 2.5 ), ,,,, that were collected from diverse regions (urban/industrial, rural/background, and coastal/offshore sites) have been reported for Hg isotope compositions. TGM samples collected at inland background sites (e.g., forested mountains) far from the urban/industrial centers and tectonically active regions (e.g., volcanos and faults) are commonly characterized by positive δ 202 Hg (−0.16 to 1.19‰, site-specific mean values) and slightly negative Δ 199 Hg (−0.28 to −0.05‰) and Δ 200 Hg (−0.11 to −0.02‰) values (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Atmospheric samples, including TGM (typically used to represent GEM) , , and PBM of different particulate sizes (TSP, PM 10 , and PM 2.5 ), ,,,, that were collected from diverse regions (urban/industrial, rural/background, and coastal/offshore sites) have been reported for Hg isotope compositions. TGM samples collected at inland background sites (e.g., forested mountains) far from the urban/industrial centers and tectonically active regions (e.g., volcanos and faults) are commonly characterized by positive δ 202 Hg (−0.16 to 1.19‰, site-specific mean values) and slightly negative Δ 199 Hg (−0.28 to −0.05‰) and Δ 200 Hg (−0.11 to −0.02‰) values (Figure ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…89−92 A previous study 89 has reported that the feathers and blood of Adeĺie penguins in the Adeĺie Land (Antarctic Zone, 66°40′S, 140°10′E) exhibit a high proportion of MeHg (93 ± 6%, mean ± 1SD, n = 20), as 69 while "GWS TGM" represents atmospheric total gaseous Hg at Great Wall Station in Antarctica. 82 "Antarctic sediment" represents the coastal sediments of King George Island, Antarctica. 76 Literature for Hg isotope data for other samples can be found in Table S3 well as significantly positive Δ 199 Hg (1.67 ± 0.18‰, mean ± 1SD, n = 20, Figure S6), which was interpreted to reflect the Δ 199 Hg of MeHg in the water domain that modern Adeĺie penguins prey on.…”
Section: Marine Photodemethylation Induced Significantlymentioning
confidence: 99%
“…Y. Sun et al, 2016;Yin et al, 2014Yin et al, , 2016, land surface GEM emissions (Yuan et al, 2019(Yuan et al, , 2021Zhu et al, 2022), background free tropospheric GEM pool (Fu, Jiskra, et al, 2021;Kurz et al, 2020;Nguyen et al, 2021), and atmospheric GEM at other surface sites (Demers et al, 2015;Enrico et al, 2016;Fu et al, 2018Fu et al, , 2019Fu, Jiskra, et al, 2021;Gratz et al, 2010;Jiskra et al, 2019;Kurz et al, 2020;Nguyen et al, 2021;Obrist et al, 2017;Yu et al, 2021Yu et al, , 2022. White circles within the shaded boxes indicate the median δ 202 Hg, Δ 199 Hg, and Δ 200 Hg estimated for anthropogenic emissions, land surface emissions, and background free tropospheric pool, and the shaded boxes indicate the interquartile range of estimated isotopic compositions.…”
Section: Causes Of the Changes In Gem Concentrations And Isotope Comp...mentioning
confidence: 99%